PENINGKATAN KINERJA KARYAWAN TERHADAP WIRAUSAHA LAUNDRY : STUDI KASUS LAUNDRY AMOR - Umi Khumaidah; Agus Wahyudi; Maya Suci Rahmadani; Indah Trifiana; Rifqi Puruhita (Jurnal Publikasi Manajemen Informatika, 2025)
This paper discusses the influence of work motivation and work environment on employee performance at Amor Laundry. The research shows that the provision of financial compensation in the form of decent and timely salaries and bonuses is a major factor in increasing employees' extrinsic motivation. In addition, a conducive work environment, both physical aspects such as cleanliness and facilities, as well as non-physical aspects such as good communication and moral support, also play an important role in building employees' intrinsic motivation in a sustainable manner. Effective work environment management faces challenges such as budget constraints and resistance to change, which requires a participatory approach and regular evaluation involving employees. The integration between financial compensation and the development of a supportive work environment is expected to increase job satisfaction, reduce turnover intention, and encourage increased productivity and service quality at Laundry Amor.This study uses a qualitative approach, which is a method that focuses on collecting descriptive data in the form of speech, writing, and individual behavior recorded through an in-depth observation process.